Assessing clinical preventive services of Health Centre, IIUM, Kuantan Campus - Tin , Myo Han; Abdullah, Fa’iza; Thuraiappah, D. M. (2011)
Clinical preventive services (CPS) is an important aspect of patient management. It includes counseling, screening, immunization and chemoprevention. By using electronic medical record (EMR) data in Health Centre, gives a great support in understanding the level of CPS available, the practice environment and how CPS can be improved in this setting.